Improving Student Learning Outcomes on the Material of Recognizing Capital Letters Using the Student Active Learning Approach at RA Muslimat NU 65 Faqih Hasyim - Ida Fitriyana; Heny Novita (Journal of Action Research in Islamic Education, 2025)
Efforts to Improve Learning Outcomes of Capital Letter Recognition Material Using SAL of Students in Grade Zero of RA Muslimat NU 65 Faqih Hasyim. The purpose of this study is to Improve Learning Outcomes of Capital Letter Recognition Material Using SAL of Students in Grade Zero of RA Muslimat NU 65 Faqih Hasyim. The method used in this study is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and reflection. Based on the results of the action research, SAL Type Cooperative Learning can Improve Learning Outcomes of Capital Letter Recognition Material of Students in Grade Zero of RA Muslimat NU 65 Faqih Hasyim. Furthermore, the researcher recommends: (1) For teachers who have the same difficulties, they can apply SAL Type Cooperative Learning to improve Learning Outcomes. (2) In order to get maximum results, it is hoped that teachers will make SAL Type Cooperative Learning more interesting and varied.